IL‐10 and IL‐17 expression by CD4+ T cells is altered in corticosteroid refractory immune thrombocytopenia (ITP). (28th July 2020) - Stimpson, Madeleine L.; Lait, Philippa J. P.; Schewitz‐Bowers, Lauren P.; Williams, Emily L.; Thirlwall, Kimberley F.; Lee, Richard W. J.; Bradbury, Charlotte A.
Abstract: Background: Corticosteroids remain the first‐line treatment for patients with immune thrombocytopenia (ITP). However, 20% to 30% of patients do not respond to treatment at tolerable doses. This variation in corticosteroid efficacy is replicated in other autoimmune diseases and may have an adaptive immune basis. Objective: To test the hypothesis that CD4 + T‐cell responses to corticosteroids are different in patients with clinically defined corticosteroid refractory ITP. Methods: In this prospective cohort study, CD4 + T cells from patients with ITP were cultured in the presence or absence of dexamethasone (Dex). Intracellular cytokine expression was then quantified by flow cytometry and compared with patients' clinical response to corticosteroid treatment. A control cohort of patients with autoimmune uveitis was also studied to evaluate whether our findings were limited to ITP or are potentially generalizable across autoimmune diseases. Results: The ratio of interleukin (IL)‐10 to IL‐17 expression following CD4 + T cell culture with Dex was able to discriminate between ITP patients with a clinically defined complete (n = 33), partial (n = 12) or nonresponse (n = 11) to corticosteroid treatment ( P = .002). These findings were replicated in patients with autoimmune uveitis (complete response n = 14, nonresponse n = 22; P = .01). Conclusions: There is a relative abrogation of IL‐10 and persistence of IL‐17 expression in the CD4 + T cells of patients who clinically fail corticosteroid therapy. This observation has potential to inform both our mechanistic understanding of the action of corticosteroids in the treatment of ITP, and as a biomarker for steroid refractory disease, with potential application across a range of hematological and nonhematological conditions.